Management of Acute Respiratory Infections (ARI) in Children and Environmental Risk Factors: A Literature Review - Azrin, Minalni; Sakir, Sarni; Julianas, Eva; Amanda, Isnaeni; Nadia, Putri; Fuspita Sari, Rispa; Mardiah, Ainun; Cahyana, Icha; Wanda, Irma; Purnamasari, Anisa (Nursing Genius Journal, 2025)
Background: Acute Respiratory Infections (ARI) are among the leading health problems contributing to the high mortality rate in children under five, both globally and in developing countries. ARI is a common respiratory disease that poses significant global concern due to its high morbidity and mortality rates, especially among children and the elderly. Common respiratory infections include the common cold, upper respiratory tract infections, influenza-like illnesses, and flu, which are caused by bacterial, viral, and fungal pathogens. Purpose:  The purpose of this review is to examine Acute Respiratory Infections (ARI) in children and to identify associated environmental risk factors. Methods:  A systematic literature search was conducted using several databases, including ScienceDirect and Google Scholar. The selected articles provided information on study sample size, research findings, and levels of evidence. Results:  The search process yielded 10 eligible journals that met the predetermined keywords and inclusion criteria. Conclusion:   ARI affects both the upper and lower respiratory tracts, with viral and bacterial infections being the primary causes, which are easily transmitted through airborne particles or direct contact. Environmental factors such as air pollution, exposure to cigarette smoke, the use of fossil fuels for household needs, and poor sanitation conditions are significant risk factors that exacerbate the incidence of ARI.